Análise da influência da vibração de máquina na qualidade do acabamento superficial e no surgimento de delaminação durante o fresamento lateral de laminados de CFRP (Carbon Fiber Reinforced Polymer) - Camargo, Wesley Soares (Universidade Federal de São Carlos, 2022)
The use of composite materials in the manufacture of products has grown in several sectors of the industry, which promotes research and development aimed at the improvement of these materials. However, the machining conditions imposed in the manufacturing process of a material are determining factors in the final quality of the product, due to structural changes resulting from cutting forces, vibrations and temperature, in addition to other interference generated by the process in the surface finish of the machined part. . Thus, the research project in question proposes a comparative study through combinations, involving different rates of feed speed during the machining process used in the milling of parts in CFRP laminates, a material widely used in the aeronautical manufacturing industry. Analyzes were carried out regarding the integrity of the CFRP laminate, in relation to the surface finish and delamination conditions of the composite, caused by the imposed machining conditions. At the same time, the level and characteristics of the mechanical vibration exerted in the milling were monitored, according to the different parameters of feed speed adopted, in order to allow a correlation between the different variables applied in the process. CFRP laminated specimens were milled at different feed rates keeping constant rotation, on a Romi D800 CNC machining center. During the milling process, mechanical vibration signals were captured with a MEMS ADXL335 triaxial accelerometer fixed to the milled part. A rhombic-type end mill was used during machining. To evaluate the structural results obtained on the machined surface of the milled parts, the scanning electron microscopy technique was used, showing the best finish of the machined surface with higher cutting feed rates.
Analysis of the influence of machine vibration on the quality of surface finish and in the emergence of delamination during side milling of CFRP laminates (Carbon Fiber Reinforced Polymer)
Análisis de la influencia de las vibraciones de la máquina en la calidad de acabado superficial y en la aparición de la delaminación durante el fresado lateral de laminados CFRP (Carbono Polímero Reforzado Con Fibra)
Keywords: Fresamento; CFRP; Delaminação; Vibração de máquina; Milling; CFRP delamination; Machine vibration; ENGENHARIAS::ENGENHARIA MECANICA::PROCESSOS DE FABRICACAO